Dar reči roman - Bujda, Jurij Vasilʹevič 1954- (Novaja russkaja klassika, 2023)
"The protagonist of the new novel "Gift of Speech", Ilya Shramm at 16 finds a father, a famous TV presenter, as well as a lord brother, a woman and family who loved life: the old Moscow clan of the Soviet aristocracy. Here, journalists, KGB officers and beautiful women conduct witty conversations, they are ironic and cynical, brilliantly erudite and speak several languages, are not afraid of free thought and Frondere. Each of them, in addition to general sins, has a personal set of skeletons from the past - and some secrets lead to the (19)thirties and even pre -revolutionary years ..." --